Effect of liquid and solid insecticide applications and insect behavior on Sphenophorus levis Vaurie, 1978 (Coleoptera: Curculionidae) control in sugarcane - Ferreira, Pedro Henrique Urach [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Insecticide adoption and current application methods for Sphenophorus levis Vaurie, 1978 (Coleoptera: Curculionidae) control have not been sufficient to reduce insect population due to low insecticide concentrations near the insect as a consequence of its location underneath the soil. Few information regarding the insect’s behavior is currently available and further research must be conducted to assist S. levis management in sugarcane. In addition, conventional control methods are still limited to liquid insecticide applications despite solid applications have proven effective for several soil insects and crops due to gradual insecticide release with a prolonged effect against pests. Therefore, it is extremely important to better understand S. levis behavior and to investigate the potential of solid insecticide applications for S. levis control in sugarcane. The study aimed to assess the repellency of S. levis adults from insecticides and to evaluate adults’ activity and location. In addition, the study’s objective also included evaluating the efficacy of solid and liquid application methods of different insecticides under semi-controlled conditions and field conditions during sugarcane planting and ratoon treatment. The study investigating the insect’s behavior effect was conducted in 2021 and consisted of hourly evaluations of S. levis adults in containers with sugarcane plants and soil. The semi-controlled study was conducted in 2021 and included assessing the mortality levels of S. levis adults with field-simulated applications of liquid and solid insecticides. The three field studies were conducted in 2020 with evaluations in 2020 and 2021 and consisted of assessing S. levis control, sugarcane injury level and sugarcane yield for liquid and solid applications of insecticides (thiamethoxam, fipronil, thiamethoxam + lambda-cyhalothrin, imidacloprid) and one entomopathogenic fungus (Metarhizium anisopliae). S. levis adults were not repelled nor attracted to thiamethoxam + lambda-cyhalothrin treated sugarcane stems and S. levis adults were confirmed to be nocturnal with the greatest number of exposed and active adults occurring from 18:00 pm until 2:00 am. In the field-simulated experiment, low S. levis adult mortality was detected (< 53%) but doubling the solid applied thiamethoxam + lambda-cyhalothrin dosage improved S. levis adult mortality to 76.7%. Regarding the field studies, solid insecticide applications showed great potential for S. levis control improvement in despite of an overall low S. levis control among all treatments. Soil drill applications were seen to promote better efficacy than broadcast and band spraying methods. Insecticide applications at planting and in ratoon cane were not very effective for S. levis control and frequent pest monitoring may help determining the best moment for insecticide application after planting and might help recommending a second application in ratoon cane. Therefore, positive effects from solid insecticide applications were observed indicating potential benefits for S. levis control and the necessity of further studies with appropriate granular formulations with adequate dosages and new insecticides.

O uso de inseticidas e métodos de aplicação atualmente utilizados no controle de Sphenophorus levis Vaurie, 1978 (Coleoptera: Curculionidae) não têm sido suficiente para reduzir sua população devido à baixas concentrações do inseticida como resultado de sua localização abaixo da superfície do solo. Poucas informações a respeito do comportamento do inseto estão atualmente disponíveis de modo que novas pesquisas devam ser conduzidas para auxiliar o manejo de S. levis em cana-de-açúcar. Além disso, métodos convencionais de controle ainda se limitam em aplicações líquidas de inseticidas apesar de aplicações sólidas terem se mostrado eficazes para diversas pragas de solo e culturas, devido a liberação gradual do inseticida resultando em um efeito prolongado contra as pragas. Desse modo, é extremamente importante o melhor entendimento do comportamento do S. levis, além da necessidade de se investigar o potencial de aplicações sólidas de inseticidas no controle de S. levis em cana-de-açúcar. O trabalho objetivou avaliar a repelência de adultos de S. levis a inseticidas e avaliar a atividade e localização de adultos de S. levis. O estudo também objetivou avaliar a eficácia dos métodos de aplicações de diferentes inseticidas por via líquida e sólida em condições semicontroladas e a campo durante o plantio e o tratamento de soqueiras de cana-de-açúcar. O estudo que avaliou o efeito do comportamento do inseto foi conduzido em 2021 e consistiu de avaliações horárias de adultos de S. levis em recipientes com plantas de cana-de-açúcar e solo. O estudo em condições semicontroladas foi conduzido em 2021 e incluiu avaliações de mortalidade de adultos de S. levis sob aplicações simuladas de campo com inseticidas líquidos e sólidos. Os três estudos de campo foram conduzidos em 2020 com avaliações em 2020 e 2021 avaliando o controle de S. levis, os níveis de toco atacado e a produtividade de cana-de-açúcar com aplicações líquidas e sólidas de inseticidas (tiametoxam, fipronil, tiametoxam + lambda-cialotrina, imidacloprido) e de um fungo entomopatogênico (Metarhizium anisopliae). Os adultos de S. levis não foram repelidos nem atraídos por colmos de cana-de-açúcar tratados com tiametoxam + lambda-cialotrina e confirmou-se o comportamento noturno de adultos de S. levis com maior número de adultos expostos e ativos ocorrendo das 18:00 p.m. até as 2:00 a.m. No experimento simulando aplicações a campo, detectou-se baixa mortalidade de adultos de S. levis (<53%) mas ao se dobrar a dosagem de tiametoxam + lambda-cialotrina aplicado via sólida, a mortalidade de adultos de S. levis aumentou para 76.7%. Em relação aos estudos de campo, as aplicações de inseticidas via sólida demonstraram grande potencial para aumentar o controle de S. levis apesar de uma baixa eficácia geral de todos os tratamentos. As aplicações com corte de soqueira demonstraram promover melhor eficácia do que pulverizações em área total ou em faixa. Já as aplicações de inseticidas durante o plantio e na soqueira não foram muito efetivas para o controle de S. levis enquanto que o frequente monitoramento de pragas pode ajudar a determinar o melhor momento para aplicações de inseticidas depois do plantio e pode ajudar a recomendar uma segunda aplicação em cana soca. Desse modo, observou-se efeitos positivos das aplicações de inseticidas via sólida mostrando benefícios em potencial no controle de S. levis, além da necessidade de novos estudos com formulações sólidas apropriadas, com dosagens adequadas e com novos inseticidas.
Efeito de aplicações líquidas e sólidas de inseticidas e do comportamento do inseto no controle de Sphenophorus levis Vaurie, 1978 (Coleoptera: Curculionidae) em cana-de-açúcar
Keywords: Granular; Billbug; Weevil; Ratoon; Residue; Mortality; Inseticidas; Cana-de-açúcar